Upaya Mahasiswa dalam Meningkatkan Semangat Belajar Siswa dan Mengentaskan Buta Huruf Al-Qur’an di Desa Pondok Kresek Kabupaten Rokan Hilir - Aidil Halim Lubis; Novita Sari; Nur Aslamiyah; Siti Qomariah Dalimunte; Anggriani (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The problem that occurs in Pondok Kresek village, Rokan Hilir Regency is the low enthusiasm of students in learning and eradicating illiteracy in the Qur'an. The purpose of this study was to motivate students in the academic field and to find out the empowerment of the Pondok Kresek village community in order to eradicate illiteracy in the Qur'an. Student activities that are specifically for undergraduate students and must be followed as a graduation requirement. The method used in this study is a qualitative method, which means the implementation of research that can produce descriptive data belonging to the spoken and written words of someone who has been observed. In this study, there are techniques for collecting data by observing, and documenting and using descriptive methods which are carried out by students directly. The implementation of the spirit of learning motivation is carried out by inviting students to learn while playing, learning while telling stories by sharing experiences and learning while taking quizzes with those who can answer the quiz get prizes. The process of learning Al Qur'an illiteracy begins with introducing hijaiyah letters and teaching tajwid. As well as holding the 1 Muharram competition with the theme